Nutritional Therapy in Crohn’s Disease – A Review of Current Trends and Evidence - Solarz, Justyna Maria; Wawrzyńców, Jakub Tomasz; Cyrkler, Weronika; Robak, Jakub; Telega, Stanisław; Bollin, Paweł; Szymczak, Urszula; Lachór, Wojciech Wiesław; Solarz, Monika Barbara; Piekarska, Julia (Quality in Sport, 2025)
Crohn’s disease (CD) is a chronic inflammatory bowel disease with a complex etiology. Although standard pharmacological treatment effectively controls the disease, increasing attention is being given to nutritional therapy as an adjunctive or alternative method. Exclusive enteral nutrition (EEN) is the most effective dietary intervention in children; however, its restrictive nature limits its use in adults. The Crohn’s Disease Exclusion Diet (CDED) combined with partial enteral nutrition (PEN) demonstrates effectiveness similar to EEN, with better patient acceptance. The Mediterranean Diet (MD) and Specific Carbohydrate Diet (SCD) may support remission, but there is insufficient evidence of their long-term efficacy. The low FODMAP diet reduces gastrointestinal symptoms, but its effect on inflammation remains unconfirmed. A significant challenge in treatment is malnutrition, which is common in CD patients and requires individual assessment and supplementation. Nutritional therapy represents a promising treatment strategy for CD, but its effectiveness requires further investigation.